Low foristic richness of afro‐alpine vegetation of Mount Kenya is related to its small area - Nyaga, Justine M.; Onipchenko, Vladimir G.; Kopylova, Natalia A.; Kipkeev, Alii M.; Elumeeva, Tatiana G.; Azovsky, Andrei; Dudov, Sergei V. (Springer, 2019)
Diversity patterns of tropical alpine vegetation is poorly studied. We estimated vascular plant floristic richness for two typical afro-alpine communities in Mount Kenya using a series of nested plots sized from 25 to 100 m2. The α-diversity was low for all plot sizes (4.8–7.8 and 12.8 species per one and 100 m2, respectively). Comparative analysis of α-, β- and γ-diversity across 22 plant communities from five Mountain regions (Mount Kenya, European Alps, Caucasus, Tibet, New Zealand Alps) revealed that area of mountain system was the only significant variable shaping the local richness; this effect became stronger with increasing spatial scale. Beta-diversity, by contrast, showed neither latitudinal trends nor significant correlation with other geographical or climatic variables. We conclude that the total area of mountain system is one of the main factors determining the regional species pool and, ultimately, the local diversity of alpine plant communities (the “echo-effect”). Small area and isolation of Mt. Kenya are considered as the main reasons for low local richness of its afro-alpine vegetation.
Keywords: Species–area relationship; Floristic richness; Alpha-diversity; Beta-diversity; Mt. Kenya; Afro-alpine; Tropical alpine · Plant communities